2012
DOI: 10.1111/j.1556-4029.2012.02085.x
|View full text |Cite
|
Sign up to set email alerts
|

The Forensic Deaths Caused by Pesticide Poisoning Between the Years 2006 and 2009 in Izmir, Turkey*

Abstract: Pesticide poisoning is still a significant health problem in Turkey. We conducted a retrospective study of autopsy cases at Izmir Branch of the Council of Forensic Medicine to describe the characteristics of deaths caused by pesticide poisoning between 2006 and 2009. The distributions of the cases according to gender and age were as follows: men 74.1% (n = 40, mean [±SD] age, 44.7 ± 14.1), women 25.9% (n = 14, mean [±SD] age, 39.2 ± 18.9). The majority of pesticide-poisoning deaths were suicides (n = 43, 80%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…Moreover, another study in Costa Rica reported that professional poisonings were the third most frequently seen poisoning type, after poisonings to commit suicide and accidentally (49). It has also been reported in other studies that 60-80% of pesticide poisonings were the result of a suicide attempt (31,38,40,50). Other studies in the literature support our finding that accidental poisoning is the second most common type, following suicidal poisoning (51,52).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, another study in Costa Rica reported that professional poisonings were the third most frequently seen poisoning type, after poisonings to commit suicide and accidentally (49). It has also been reported in other studies that 60-80% of pesticide poisonings were the result of a suicide attempt (31,38,40,50). Other studies in the literature support our finding that accidental poisoning is the second most common type, following suicidal poisoning (51,52).…”
Section: Discussionsupporting
confidence: 91%
“…In the study, which differed from our findings, it was determined that the pesticide poisoning cases occurred most often in the summer and winter months (39). It was reported that they occurred most often in the spring and summer, and that the deaths due to pesticide poisoning reached the highest level in June (40). In addition, it was reported that poisoning occurred most often during the summer months (41).…”
Section: Discussionmentioning
confidence: 99%
“…Most poisoning cases by pesticides occur as a result of misuse, accidental exposure and, in cases of accidental or suicidal exposure by oral ingestion [28]. Pesticide poisoning is also one of the most common methods of suicide in developing countries [29]. Although some authors [30,31] had studied new pesticide for- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio, la frecuencia de muertes por intoxicación con plaguicidas fue mayor entre los hombres, tal como se ha reportado en otras partes del mundo (43)(44)(45), circunstancia que se ve favorecida en las áreas rurales donde existe un mayor acceso a los plaguicidas empleados en las actividades agrícolas (46).…”
Section: Discussionunclassified